Good Morning, Orthopods: The Growth and Future Implications of Podcasts in Orthopaedic Surgery. (5th May 2021) - Jella, Tarun K.; Cwalina, Thomas B.; Acuña, Alexander J.; Samuel, Linsen T.; Kamath, Atul F.
Abstract : Background: As the landscape of medical education evolves with emerging technologies and the COVID-19 pandemic, e-learning platforms continue to gain popularity. Orthopaedic podcasts, a burgeoning e-learning platform, continue to gain traction; however, there is a paucity of information regarding their coverage of topics and their distribution over time. Therefore, our analysis sought to (1) characterize podcast content related to orthopaedic surgery, and (2) evaluate the changes in the prevalence of orthopaedic podcasts over the past 15 years. Methods: Three common podcasting platforms (Apple Podcasts, Google Podcasts, and Spotify) were queried using the key terms "orthopaedic, " "orthopedic, " and "ortho" in order to identify a list of podcasts that are related to orthopaedic surgery. For each unique orthopaedic podcast, the title, the show description, the number of episodes, the date of the first episode, the date of the most recent episode, and episode frequency were collected. Podcasts were then classified based on a predetermined list of podcast domains. The number of existing active (released within the last 3 months) orthopaedic podcasts was then trended on a monthly basis from 2011 to 2020. Results: Ninety-four unique podcasts met inclusion criteria, 62 of which remained active as of October 25, 2020. The most common podcast domains were "general" (38 [40.4%]) and "clinical knowledge" (20 [21.3%]). Among the assessed podcasts, 90 (95.7%) utilized an exclusively audio format. The majority of podcasts were based in the United States (89.4%), included introductory music (72.3%), and included interviews (63.8%). Most podcast hosts were practicing orthopaedic surgeons (52.1%). Between January 2016 and October 2020, the number of active orthopaedic surgery podcasts grew more than twelvefold (1, 240%) at an average rate of roughly 1 new podcast each month (average, 1.0 podcast; standard deviation, 1.8). Discussion: The past decade has seen sizable growth in the number of readily available podcasts related to orthopaedic surgery. Additional research is required to independently assess the quality of these resources and their implications for remote trainee education.